Tracing the Roots and Gateways of Radicalization in Countering Radicalism through a System Approach at the State Islamic University of Mataram - Nazar Naamy; Abdul Razak Abdulroya Panaemalae (Edukasia Islamika, 2022)
This paper examined counter-radicalization at Mataram State Islamic University (UIN Mataram) through a systematic approach. It focused on the forms, typology, roots, and gateways of radicalism in the Islamic university. This study categorized the roots of radicalism as the internal aspect of the system, while the gateways are referred to as the external component. The findings showed that the efforts to demolish radicalism at UIN Mataram should be preceded by the understanding of (a) forms and typology of radicalism, (b) understanding of the roots and gateways of the radical ideology, and (3) offering solutions through system approach. These include leadership involvement, disseminating moderate Islamic values (Washatiyyah), re-examining the curriculum and materials prone to misunderstanding, modifying the pedagogical methods, involving Islamic boarding schools, and carrying out more studies on radicalism at Islamic higher education institutions.